The Characterization of the Toll of Caring for Coronavirus Disease 2019 on ICU Nursing Staff - Laudanski, Krzysztof; Moon, Ken; Singh, Amandeep; Chen, Ying; Restrepo, Mariana (Critical care explorations, 2021)
Coronavirus disease 2019 pandemic exercised a significant demand on healthcare workers. We aimed to characterize the toll of caring for coronavirus disease 2019 patients by registered nurses. An observational study of two registered nurses cohorts. ICUs in a large academic center. Thirty-nine ICU registered nurses assigned to coronavirus disease 2019 versus noncoronavirus disease 2019 patients. None. Skin temperature (t [°C]), galvanic skin stress response (GalvStress), blood pulse wave, energy expenditure (Energy [cal]), number of steps (hr ), heart rate (min ), and respiratory rate (min ) were collected using biosensors during the shift. National Aeronautics and Space Administration Task Loading Index measured the subjective perception of an assignment load. Elevated skin temperatures during coronavirus disease 2019 shifts were recorded (Δt vs t = +1.3 [°C]; 95% CI, 0.1-2.5). Registered nurses staffing coronavirus disease patients self-reported elevated effort (ΔEffort vs Effort = +28.6; 95% CI, 13.3-43.9) concomitant with higher energy expenditure (ΔEnergy vs Energy = +21.5 [cal/s]; 95% CI, 4.2-38.7). Galvanic skin stress responses were more frequent among coronavirus disease registered nurse (ΔGalStress vs GalvStress = +10.7 [burst/hr]; 95% CI, 2.6-18.7) and correlated with self-reported increased mental burden (ΔTLXMental vs ΔTLXMental = +15.3; 95% CI, 1.0-29.6). There are indications that registered nurses providing care for coronavirus disease 2019 in the ICU reported increased thermal discomfort coinciding with elevated energy expenditure and a more pronounced self-perception of effort, stress, and mental demand.